Trained eyes: experience promotes adaptive gaze control in dynamic and uncertain visual environments. - Shuichiro Taya (Public Library of Science (PLoS), 2013)
Current eye-tracking research suggests that our eyes make anticipatory movements to a location that is relevant for a forthcoming task. Moreover, there is evidence to suggest that with more practice anticipatory gaze control can improve. However, these findings are largely limited to situations where participants are actively engaged in a task. We ask: does experience modulate anticipative gaze control while passively observing a visual scene? To tackle this we tested people with varying degrees of experience of tennis, in order to uncover potential associations between experience and eye movement behaviour while they watched tennis videos. The number, size, and accuracy of saccades (rapid eye-movements) made around 'events,' which is critical for the scene context (i.e. hit and bounce) were analysed. Overall, we found that experience improved anticipatory eye-movements while watching tennis clips. In general, those with extensive experience showed greater accuracy of saccades to upcoming event locations; this was particularly prevalent for events in the scene that carried high uncertainty (i.e. ball bounces). The results indicate that, even when passively observing, our gaze control system utilizes prior relevant knowledge in order to anticipate upcoming uncertain event locations.